Development of Physics REACT Module Assisted With PhET Simulations on Harmonic Vibration Materials - Maryani Maryani; Novita Bekti Haryo Putri; Bambang Supriadi (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
Technology in the milenial era is developing so rapidly and has an impact on the world of education. The world of education is required to harmonize learning methods and media used with technological development. The lack of direct practicum activities in several schools has resulted in students' understanding of the material presented not as expected. Physics REACT module assisted by PhET simulations on harmonic vibration material can be a solution for delivering harmonious vibration material with practically practicum activities. This study aims to determine the validity of the modules that have been developed and the effectiveness of the modules. This research includes development research using the Nieveen development design. This module is equipped with explanations in accordance with the REACT approach and practicum activities using PhET. The subjects of this study were students of class XI IPA 3 at SMAN Bandarkedungmulyo Jombang. The results of expert validation were 94.4% with the very feasible / valid category, while the results of user validation were 96.09% with the very feasible / valid category. Student physics learning outcomes have increased, this can be seen from the acquisition of N-Gain in the limited test of 0.6 in the medium category and in the field test of 0.7 in the high category. Not only N-Gain method, you can also use the t-test. It can be concluded that the REACT physics module assisted by PhET simulations on harmonic vibration material is very feasible and effective to be used in the learning process.